Fe, Cu‐Coordinated ZIF‐Derived Carbon Framework for Efficient Oxygen Reduction Reaction and Zinc–Air Batteries - Wang, Zhihao; Jin, Huihui; Meng, Tian; Liao, Ke; Meng, Wenqian; Yang, Jinlong; He, Daping; Xiong, Yuli; Mu, Shichun (Advanced functional materials, 2018)
Zeolitic imidazole frameworks (ZIFs) offer rich platforms for rational design and construction of high‐performance nonprecious‐metal oxygen reduction reaction (ORR) catalysts owing to their flexibility, hierarchical porous structures, and high surface area. Herein, an Fe, Cu‐coordinated ZIF‐derived carbon framework (Cu@Fe‐N‐C) with a well‐defined morphology of truncated rhombic dodecahedron is facilely prepared by introducing Fe2+ and Cu2+ during the growth of ZIF‐8, followed by pyrolysis. The obtained Cu@Fe‐N‐C, with bimetallic active sites, large surface area, high nitrogen doping level, and conductive carbon frameworks, exhibits excellent ORR performance. It displays 50 mV higher half‐wave potential (0.892 V) than that of Pt catalysts in an alkaline medium and comparable performance to Pt catalysts in an acidic medium. In addition, it also has excellent durability and methanol resistance ability in both acidic and alkaline solutions, which makes it one of the best Pt‐free catalysts reported to date for ORR. Impressively, when being employed as a cathode catalyst in zinc–air batteries, Cu@Fe‐N‐C presents a higher peak power density of 92 mW cm−2 than that of Pt/C (74 mW cm−2) as well as excellent durability. Fe, Cu‐coordinated zeolitic imidazole framework–derived carbon framework shows a superior oxygen reduction reaction performance with a half‐wave potential of 0.892 V, 50 mV higher than Pt/C, and excellent stability, resulting from bimetallic active sites, high active N content, and the mesoporous architecture. When employed as cathode catalyst, it also displays a good Zn–air battery performance.